Power concavity in weakly coupled elliptic and parabolic systems. (January 2016) - Ishige, Kazuhiro; Nakagawa, Kazushige; Salani, Paolo
Abstract: In this paper we start the investigation of concavity properties of solutions to systems of PDE's in convex domains. In particular we prove that suitable powers of solutions to some weakly coupled elliptic and parabolic systems are concave.